Short-Term Outcomes and Influencing Factors After Ankle Fracture Surgery - Sung, Ki Hyuk; Kwon, Soon Sun; Yun, Yeo Hon; Park, Moon Seok; Lee, Kyoung Min; Nam, Muhyun; Jung, Jae Hong; Lee, Seung Yeol (Journal of Foot and Ankle Surgery, 2018)
The present study investigated the factors influencing the early clinical outcomes after ankle fracture surgery. We included 88 patients, who had undergone implant removal surgery at 1 year after ankle fracture surgery, with ankle computed tomographic (CT) scans obtained before ankle fracture surgery and at implant removal available. We collected demographic information, including age, sex, the presence of diabetes mellitus, level of trauma energy, and fracture classification from the medical records. We also recorded the fracture height using the radiographs and CT images. The medial joint space and articular incongruity were assessed on the follow-up radiographs and CT scans. Bone attenuation was measured by placing a circular region of interest around the ankle joint on the preoperative CT image. The postimplant removal outcomes were assessed using 2 functional questionnaires, the American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot scale and Foot and Ankle Outcome Score (FAOS). Significant factors related to the AOFAS ankle-hindfoot scale scores and FAOS were identified through univariate analysis using age, sex, radiographic measurements, and CT findings as explanatory variables, followed by multiple regression analysis. On multiple regression analysis, the total FAOS was independently related to the AO classification (p =.003) and Lauge-Hansen classification (p =.003). The total AOFAS ankle-hindfoot scale score was related to articular incongruity (p =.044). The early clinical outcomes after ankle fracture surgery were affected by involvement of the ankle joint fracture rather than the lateral malleolus fracture height. Female sex and the presence of postoperative articular incongruity correlated with inferior early clinical outcomes.
Keywords: Adolescent; Adult; Aged; Ankle Fractures; Female; Fracture Fixation, Internal; Humans; Male; Middle Aged; Range of Motion, Articular; Regression Analysis; Retrospective Studies; Time Factors; Tomography, X-Ray Computed; Treatment Outcome; Young Adult; 3; ankle fracture; AO classification; AOFAS scale; FAOS; Lauge-Hansen classification